2015
DOI: 10.1007/s12262-015-1422-5
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Closure of 61 Open Abdomen Patients Based on an Algorithm

Abstract: Hemodynamic resuscitation, source control, and delayed abdominal closure are the three fundamental steps for open abdomen (OA) management. When to start delayed abdominal closure and how to determine which delayed closure method should be applied to each OA patient are not clarified in the literature. We evaluated an algorithm that was developed to address these two questions. A retrospective chart review was conducted for OA patients treated for according to the algorithm. When hemodynamic stabilization and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…In total, 13 studies fulfilled the criteria [12][13][14][15][16][17][18][19][20][21][22][23][24]. All included studies are observational cohort studies, and no studies reported on the use of either the Wittmann patch or the ABRA system.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In total, 13 studies fulfilled the criteria [12][13][14][15][16][17][18][19][20][21][22][23][24]. All included studies are observational cohort studies, and no studies reported on the use of either the Wittmann patch or the ABRA system.…”
Section: Resultsmentioning
confidence: 99%
“…Two studies reported on the ABRA system in combination with NPWT [12,13], while 9 reported on meshmediated fascial traction (MMFT) combined with NPWT [14][15][16][17][18][19][20][21][22]. Other types of fascial traction, either by dynamic suture lines [23] or by a self-made silastic tube system, and NPWT [24] were reported in 2 studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…When NPT was combined with the strategies allowing reapproximation of the fascial edges, high closure rates can be achieved [15]. Use of mesh-mediated fascial traction methods may be more suitable in non-infected OA patients, whereas ABRA might be used in the severely infected OA patients in conjunction with NPT [16]. Dynamic traction adjusted continuously with ABRA in conjunction with NPT prevents fascial retraction, subscribes improvement in granulation tissue, allowing expansion and retraction during spontaneous respiratory cycle [3,4,17].…”
Section: Discussionmentioning
confidence: 99%
“…Second one is the significant decrease in mortality rate of OA patients due to evolution in the delayed abdominal closure systems and intensive care unit (ICU) consideration. [3][4][5] As the number of surviving OA patients increases, management of some challenging sequels after OA treatment, such as incisional hernia (IH), constant or permanent stoma, entero-cutaneous fistula (ECF), short bowel syndrome, chronic organ failure and badly healed scar come into consideration. 4 Most important one of them is planned or unplanned IH.…”
Section: Introductionmentioning
confidence: 99%